A review on synthesis and antibacterial potential of bio-selenium nanoparticles in the food industry - Ao, Bo; Du, Qingquan; Liu, Decheng; Shi, Xiaoshan; Tu, Junming; Xia, Xian (Frontiers in Microbiology, 2023)
Effective control of foodborne pathogen contamination is a significant challenge to the food industry, but the development of new antibacterial nanotechnologies offers new opportunities. Notably, selenium nanoparticles have been extensively studied and successfully applied in various food fields. Selenium nanoparticles act as food antibacterial agents with a number of benefits, including selenium as an essential trace element in food, prevention of drug resistance induction in foodborne pathogens, and improvement of shelf life and food storage conditions. Compared to physical and chemical methods, biogenic selenium nanoparticles (Bio-SeNPs) are safer and more multifunctional due to the bioactive molecules in Bio-SeNPs. This review includes a summarization of (1) biosynthesized of Bio-SeNPs from different sources (plant extracts, fungi and bacteria) and their antibacterial activity against various foodborne bacteria;(2) the antibacterial mechanisms of Bio-SeNPs, including penetration of cell wall, damage to cell membrane and contents leakage, inhibition of biofilm formation, and induction of oxidative stress; (3) the potential antibacterial applications of Bio-SeNPs as food packaging materials, food additives and fertilizers/feeds for crops and animals in the food industry; and (4) the cytotoxicity and animal toxicity of Bio-SeNPs.The related knowledge contributes to enhancing our understanding of Bio-SeNP applications and makes a valuable contribution to ensuring food safety.